A novel aerodynamic controllable roof for improving performance of INVELOX wind delivery system. Issue 3 (June 2021) - Golozar, Ali; Shirazi, Farzad A; Siahpour, Shahin; Khakiani, Fardad N; Gaemi Osguei, Kambiz
INVELOX is a patented structure designed to capture the incident wind from every direction, guide the collected wind to the ground level, and increase its velocity. A novel mechanism called aerodynamic controllable roof structure is introduced to improve the wind stream performance of INVELOX. The advantages of aerodynamic controllable roof structure are twofold: improving efficiency and preventing wind escaping the system. Using aerodynamic controllable roof structure, a performance curve is obtained that can improve the system efficiency. Wind speed and orientation and structural deflection are the parameters that direct the roof orientation. Fuzzy control is utilized in a model structure to control the roof movements using two servo motors. Computational fluid dynamics simulations are done to validate the performance and capability of the aerodynamic controllable roof structure mechanism. Results show that the fuzzy control is successful in controlling the roof orientation and the results from the simulation indicate that the efficiency of the system can be increased up to 12%.